Assessing the Impact of Laboratory Activities on the topic of Viscosity and Fluidity in the Classroom through Practical Applications on Everyday Objects for Vocational Students to Support Sustainable Development Goals (SDGs) - Wahyuni, Diah; Nahadi, N.; Riandi, R.; Nandiyanto, Asep Bayu Dani (Journal of Engineering Education Transformations, 2025)
The purpose of this study was to assess the impact of laboratory activities using everyday objects on the topics of viscosity and fluidity to improve vocational students’ understanding of supporting education for sustainable development. The method used in this study was a descriptive quantitative analysis design. The subjects of this study were 23 vocational students in Cimahi, West Java. Data were collected through pretest and posttest activities in the form of comprehension ability questions on the topic of viscosity and fluidity. The results obtained after conducting laboratory activities, there is an increase with a p-value <0.05. These results were analyzed using the calculation of Wilcoxon parametric statistical analysis. Laboratory activities using everyday objects can improve the understanding of vocational students on the viscosity and fluidity of material. This research is also useful to provide awareness to students by using everyday objects in science learning, this can be applied as a form of innovative pedagogy that supports education for sustainable development.